Comparison of the inducibility of CYP mRNA exposed to typical inducers in fresh and cryopreserved cynomolgus monkey hepatocytes. Issue 3 (June 2020) - Koeda, Akiko; Iwao, Takahiro; Nakanishi, Anna; Mizuno, Shota; Yamashita, Misaki; Sakai, Yoko; Nakamura, Katsunori; Matsunaga, Tamihide
Abstract: Herein, we evaluated CYPs and their nuclear receptor mRNA induction by exposure to typical inducers, omeprazole, rifampicin, and phenobarbital in cynomolgus monkey hepatocytes. Six freshly-isolated hepatocytes and 6 cryopreserved hepatocytes from cynomolgus monkey liver were prepared for a 14-day monolayer culture, 28-day co-culture with feeder cells, and 28-day 3D spheroid culture with feeder cells. Omeprazole and rifampicin respectively induced CYP1A1 and CYP3A8 mRNAs, while phenobarbital induced CYP2C43, CYP2C75, and CYP3A8, and slightly induced CYP2B6 . The nuclear receptors AHR, PXR, and CAR mRNA levels, which were activated by omeprazole, rifampicin, and phenobarbital, respectively, tended to decrease via exposure to inducers despite the increase in CYP mRNA levels. These trends were similar for all three culture methods. No evident difference was observed in CYP mRNA induction between fresh and cryopreserved hepatocytes. Based on mRNA levels, the co-culture and 3D spheroid culture methods are more reasonable than monolayer culture for CYP evaluation, because the use of feeder cells can reduce the number of hepatocytes, improve the cell adhesion, and maintain the mRNA expression levels. In addition, co-culture method is more cost-effective, as common culture plates can be used. Graphical abstract: Image 1